Ecotourists and views of nature - Hughes, Michael (Edgar Elgar Books, 2013)
Ecotourism is one form of nature-based tourism. It is generally considered a niche market involving smaller groups and specialized experiences. The first part of this book provides a detailed and extensive discussion of the definition, origins and characteristics of ecotourism. For the purposes of this chapter, a brief reiteration of the central characteristics of ecotourism is necessary for context. Defining ecotourism has been somewhat of an academic cottage industry with more than 80 definitions over recent decades (Fennell, 2001; Krider, Arguello, Campbell & Mora, 2010). The idea of ecotourism was popularized in the 1980s, with a growing awareness of concepts such as sustainability. It is intended to provide benefits both to the tourist and the location visited (Gurung & Seeland, 2008). Analysis of the numerous ecotourism definitions by Blamey (1997), Fennell (2001) and Krider et al. (2010) noted three central components.